2020
DOI: 10.1016/j.cmi.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection and electrocardiogram abnormalities: baseline assessment from the CHART cohort

Abstract: Objectives: To investigate the prevalence of various electrocardiogram (ECG) abnormalities among HIVpositive and HIV-negative individuals. Methods: This cross-sectional evaluation included 1412 HIV-positive and 2824 HIV-negative participants aged 18 to 75 years and frequency matched by age and sex, derived from the baseline survey of Comparative HIV and Aging Research in Taizhou (CHART), China, between February and December 2017. Results: HIV-positive individuals had higher prevalence of sinus tachycardia (5.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
(32 reference statements)
3
9
1
Order By: Relevance
“…Longer HIV duration (≥5 years) was positively associated with ST interval (representing ventricular repolarisation) in the current study. Our findings support the results of a study by Ding et al [ 24 ], who showed that ST/T wave abnormalities were positively associated with HIV infection, ACR, Hb, fasting glucose and longer duration of HIV infection (≥3 years). ST/T wave abnormalities have been associated with the risk of developing ventricular tachycardia, myocardial ischaemia, myocardial infarction, and abnormal ventricular repolarisation [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Longer HIV duration (≥5 years) was positively associated with ST interval (representing ventricular repolarisation) in the current study. Our findings support the results of a study by Ding et al [ 24 ], who showed that ST/T wave abnormalities were positively associated with HIV infection, ACR, Hb, fasting glucose and longer duration of HIV infection (≥3 years). ST/T wave abnormalities have been associated with the risk of developing ventricular tachycardia, myocardial ischaemia, myocardial infarction, and abnormal ventricular repolarisation [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…ST/T wave abnormalities have been associated with the risk of developing ventricular tachycardia, myocardial ischaemia, myocardial infarction, and abnormal ventricular repolarisation [ 25 ]. This finding, however, contradicts Ding et al [ 24 ], who reported significant associations between blood pressure categories and ventricular abnormalities (ST/T abnormalities) in their HIV− group instead. Soliman et al [ 26 ], reported that ST/T abnormalities, in particular, may be predictive of CVD in PWH and highlighted the prognostic value of ST/T changes in HIV+ patients.…”
Section: Discussioncontrasting
confidence: 92%
“…Those studied by His and Lamb were active Air Force personnel, while those in the current study were mainly civilians. In another study in China in adults [15], the prevalence of sinus bradycardia and sinus tachycardia in non-HIV positive subjects followed a similar pattern recorded in this study in which the prevalence of sinus bradycardia was higher than the prevalence of sinus tachycardia (prevalence of bradycardia, 9.4%; prevalence of tachycardia, 1.3%).…”
Section: Discussionsupporting
confidence: 85%
“…Data for this analysis were derived from a cross‐sectional, baseline evaluation of PLWH and HIV‐negative individuals enrolling in an ongoing prospective cohort study of HIV and age‐related co‐morbidities (Comparative HIV and Aging Research in Taizhou, or CHART) in Taizhou prefecture of Zhejiang Province in eastern China [24,25]. From February 2017, we consecutively recruited PLWH (≥18 years) to CHART when they came to local Centres for Disease Control and Prevention to receive regular follow‐up medical care and assessments [23,28].…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, China had eliminated the CD4 count thresholds on HIV treatment initiation, and treatment coverage for PLWH increased from 67% in 2015 to 83.4% in 2018 [23]. In our recent reports, subclinical atherosclerosis and electrocardiographic abnormalities were more prevalent among PLWH than among HIV‐negative individuals [24,25], emphasizing the urgent needs to address the cardiovascular risk among PLWH. The Chinese government has launched community‐based standardized BP management programmes over the past decade [26].…”
Section: Introductionmentioning
confidence: 99%